PERHITUNGAN SUHU ELEMEN BAKAR REAKTOR TRIGA 2000 DALAM TABUNG SIPPING TEST MENGGUNAKAN CFD - A., Sudjatmi K. (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
It has been calculated the fuel element temperature in the sipping test of Bandung TRIGA 2000 reactor. The calculation needs to be done to ascertain that the fuel element temperatures are below or at the limit of the allowable temperature fuel elements during reactor operation, ensuring that the implementation of the test by using this device, the temperature is still within safety limits. The calculation is done by making a model sipping test tubes containing a fuel element surrounded by 9 fuel elements, according to the position sipping test tubes in the reactor core, by using Gambit. Dimensional model adapted to the dimensions of the tube and the fuel element in the reactor core of Bandung TRIGA 2000 reactor. Sipping test Operation for each fuel element performed for 30 minutes at 300 kW power. Calculations were performed using CFD software and as input adjusted parameters of TRIGA 2000 reactor. Simulations carried out on the operation of the 30, 60, 90, 120 150, 180 and 210 minutes. The calculation result shows that the temperature of the fuel in tubes sipping test of 236,06 oC, while the temperature of the wall is 87,58 oC . The maximum temperature in the fuel center of TRIGA 2000 reactor in normal operation is 650 oC, and the boiling is not allowed in the reactor. So it can be concluded that the operation of the sipping test device are is very safe because the fuel center temperature is below the temperature limits the allowable fuel under normal operating conditions as well as the fuel element wall temperature is below the boiling temperature of water.